A new method for resolving uncertainty of energy requirements in large water breathers: the 'mega‐flume' seagoing swim‐tunnel respirometer. Issue 6 (14th March 2015) - Payne, Nicholas L.; Snelling, Edward P.; Fitzpatrick, Richard; Seymour, Jamie; Courtney, Robert; Barnett, Adam; Watanabe, Yuuki Y.; Sims, David W.; Squire, Lyle; Semmens, Jayson M.
Summary: Body size is a key determinant of metabolic rate, but logistical constraints have led to a paucity of energetics measurements from large water‐breathing animals. As a result, estimating energy requirements of large fish generally relies on extrapolation of metabolic rate from individuals of lower body mass using allometric relationships that are notoriously variable. Swim‐tunnel respirometry is the 'gold standard' for measuring active metabolic rates in water‐breathing animals, yet previous data are entirely derived from body masses <10 kg – at least one order of magnitude lower than the body masses of many top‐order marine predators. Here, we describe the design and testing of a new method for measuring metabolic rates of large water‐breathing animals: a c . 26 000 L seagoing 'mega‐flume' swim‐tunnel respirometer. We measured the swimming metabolic rate of a 2·1‐m, 36‐kg zebra shark Stegostoma fasciatum within this new mega‐flume and compared the results to data we collected from other S. fasciatum (3·8–47·7 kg body mass) swimming in static respirometers and previously published measurements of active metabolic rate measurements from other shark species. The mega‐flume performed well during initial tests, with intra‐ and interspecific comparisons suggesting accurate metabolic rate measurements can be obtained with this new tool. Inclusion of our data showed that the scaling exponent of active metabolic rate with mass for sharks ranging from 0·13 to 47·7 kg was 0·79; a similar value to previous estimates for resting metabolic rates in smaller fishes. We describe the operation and usefulness of this new method in the context of our current uncertainties surrounding energy requirements of large water‐breathing animals. We also highlight the sensitivity of mass‐extrapolated energetic estimates in large aquatic animals and discuss the consequences for predicting ecosystem impacts such as trophic cascades.